Green microwave switching from oxygen rich yellow anatase to oxygen vacancy rich black anatase TiO2 solar photocatalyst using Mn(ii) as 'anatase phase purifier'. Issue 45 (2nd November 2015) - Ullattil, Sanjay Gopal; Periyat, Pradeepan
Abstract : Green and rapid microwave synthesis of 'yellow oxygen rich' and 'black oxygen vacancy rich' anatase TiO2 solar photocatalysts. Abstract : Green and rapid microwave syntheses of 'yellow oxygen rich' (YAT-150) and 'black oxygen vacancy rich' (BAT-150) anatase TiO2 nanoparticles are reported for the first time. YAT-150 was synthesized using only titanium(iv ) butoxide and water as precursors. The in situ precursor modification by Mn(ii ) acetate switched anatase TiO2 from YAT-150 to BAT-150. The entry of Mn 2+ into the crystal lattice of anatase TiO2 paved the way for peak texturing in the existing peak orientations along with the origin of three new anatase TiO2 peaks in the (103), (213) and (105) directions. The as synthesized ultra-small (∼5 nm) yellow and black anatase TiO2 nanoparticles were found to be two fold and four fold more photoactive than the commercially available photocatalyst Degussa-P25 under sunlight illumination.